The Influence of Service Quality and Promotion on Customer Decisions: Study on One of The Islamic Banking in Bandung - Deani Dhiwanti; Soelaeman Sukmalana (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
One of the essential factors in marketing the Islamic banking sector is the customer's decision to save. This study aims to determine the effect of service quality and promotion on customer decisions to save. For this reason, the researcher uses a survey approach to nasals at one of the Islamic banking in Bandung City with 100 customers as respondents. This study uses a descriptive and verification approach to answer the posed problem formulation. The study results indicate that there is a significant effect of service quality and promotion on customer decisions to save. The results of the study recommend promoting through social media such as Instagram Ads, Facebook Ads, and Youtube Ads and increasing QRIS merchants to attract new customers under the age range of 30 years.